2017
DOI: 10.1177/2332858416686046
|View full text |Cite
|
Sign up to set email alerts
|

Beyond “Just Do It”

Abstract: Study abroad is believed to be a transformative learning experience for students. However, the extent to which study abroad adds value beyond what is possible on campus needs to be demonstrated. In this paper, we document the learning outcomes assessment undertaken by a faculty-led study-abroad program at a large university in the U.S. Southeast. Specifically, we describe the development of a theory-based pedagogical model of global citizenship for short-term study abroad and efforts to document student learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…From the perspectives of the program instructors in this study, intercultural learning was an implicit or secondary learning outcome to disciplinary knowledge and skill attainment. Still, past research has found that intentional program objectives and pedagogical design that are related to global and intercultural learning help guide desired student outcomes in this area (Landon, Tarrant, Rubin, & Stoner, 2017;Vande Berg et al, 2009). Thus, anticipated, future work of the program includes a comprehensive intervention program accompanied by assessments to measure more adequately students' intercultural development.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspectives of the program instructors in this study, intercultural learning was an implicit or secondary learning outcome to disciplinary knowledge and skill attainment. Still, past research has found that intentional program objectives and pedagogical design that are related to global and intercultural learning help guide desired student outcomes in this area (Landon, Tarrant, Rubin, & Stoner, 2017;Vande Berg et al, 2009). Thus, anticipated, future work of the program includes a comprehensive intervention program accompanied by assessments to measure more adequately students' intercultural development.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should explore the kind of GES content that can increase global citizenship in students. As noted by others (e.g., Landon et al, 2017;Tarrant et al, 2014), such content would need to reflect a deliberate integration of academic and field components. Although the present study was not designed to assess the GES program, we suspect that a more deliberate infusion of themes associated with global citizenry in both the academic and service learning components may yield different results for GES participants.…”
Section: Discussionmentioning
confidence: 99%
“…Their proliferation has led to increased conversation within and across fields (such as global education, study abroad, international service learning, and academic areas such as business, geography, and social work) about elements that are more successful at fostering desired student outcomes. Regarding student learning outcomes related to global citizenship, a majority of studies on short-term study abroad report increases in outcomes such as global awareness (Chieffo & Griffiths, 2004;Kurt, Olitsky, & Geis, 2013;Wang, Peyvandi, & Coffey, 2014), intercultural, personal and professional competencies (Drnach, Ruby, Kluender, Palomba, & Ursick et al, 2016;Zamastil-Vondrova, 2005), pro-environmental behavioral intentions (Landon, Tarrant, Rubin, & Stoner, 2017;Tarrant et al, 2014), global-mindedness (Kehl & Morris, 2008), and some forms of civic engagement (Mulvaney, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Most study abroad programs are organized as a summer course, which allows more time to make travel arrangements. Although longer programs have a greater impact on a student's education [15], they do not necessarily lead to a significant increase in competence [16]. A short period of study abroad in the form of a micro-semester in nursing curricula was reported to help students expand their views on global health care issues [2].…”
Section: Introductionmentioning
confidence: 99%